Research note: Genetically diverse avian hepatitis E virus identified in chickens with hepatitis-splenomegaly syndrome in Guangdong Province, China - Xue-Lian Zhang; Yu-Qian Zhang; Chun-Hong Liu; Yan Ma; Shu-Jian Huang; Jian-Wei Shao (Poultry Science)
Avian hepatitis E virus (HEV) is recognized as the primary causative agent of big liver and spleen disease, hepatitis-splenomegaly syndrome, and hepatic rupture hemorrhage syndrome, resulting in substantial economic losses within the global poultry industry. Since its discovery in 1991, diverse strains of avian HEV have been extensively identified worldwide. Epidemiological investigations have demonstrated the wide distribution and genetic diversity of avian HEV strains in China. In this study, avian HEV strains were identified in chickens exhibiting hepatitis-splenomegaly syndrome in Guangdong province, China. Sequence analysis indicated that these strains shared the highest nucleotide sequence identities with genotype 3 strains, and phylogenetic analysis demonstrated that they clustered with strains belonging to avian HEV genotype 3. Moreover, a statistically supported recombination event was detected within one of the avian HEV strain identified in this study. These findings significantly enhance our understanding of the genetic diversity and evolution of avian HEV in chickens, providing new insights for disease prevention and control strategies.